2015
DOI: 10.3109/14992027.2014.996826
|View full text |Cite
|
Sign up to set email alerts
|

The bone conduction implant: Clinical results of the first six patients

Abstract: Objective: To investigate audiological and quality of life outcomes for a new active transcutaneous device, called the bone conduction implant (BCI), where the transducer is implanted under intact skin. Design: A clinical study with sound field audiometry and questionnaires at six-month follow-up was conducted with a bone-anchored hearing aid on a softband as reference device. Study sample: Six patients (age 18–67 years) with mild-to-moderate conductive or mixed hearing loss. Results: The surgical procedure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 36 publications
4
44
0
Order By: Relevance
“…29 New submerged active and passive bone conduction devices that result in intact skin have been introduced in the last few years. 39,40 Even though they seem like good alternatives, they may provide too low amplification for some patients.…”
Section: Perspectivementioning
confidence: 99%
“…29 New submerged active and passive bone conduction devices that result in intact skin have been introduced in the last few years. 39,40 Even though they seem like good alternatives, they may provide too low amplification for some patients.…”
Section: Perspectivementioning
confidence: 99%
“…One such application is in a new bone conduction hearing implant system for rehabilitation of patients with mixed or conductive hearing loss, see Eeg-Olofsson et al (2014) and Reinfeldt et al (2014) for more details.…”
mentioning
confidence: 99%
“…The surgical method and audiological results of the first patient have been presented by Eeg-Olofsson et al (2014). Audiological and quality of life outcomes with the BCI on the first six patients have been addressed in a clinical study by Reinfeldt et al (2015b). In this study it was shown that the BCI improvement over the unaided condition was statistically significant in all audiometric measures.…”
Section: Summary Of Ongoing Clinical Studymentioning
confidence: 91%
“…The BCI has been introduced as an alternative to the percutaneous BAHA (Håkansson et al, 2008(Håkansson et al, , 2010Håkansson, 2011;Taghavi et al, 2012b;2012c, Eeg-Olofsson et al;2014;Reinfeldt, 2015b), and the principal design of the BCI system is shown in Figure 1. For the BCI, the skin and subcutaneous tissues are kept intact and no screw attachment to the skull bone is needed.…”
Section: The Bone Conduction Implantmentioning
confidence: 99%
See 1 more Smart Citation